2021
DOI: 10.1021/acscatal.0c04647
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning the Molecular Choreography to Prevent Hydroxylation in Germacradien-11-ol Synthase Catalysis

Abstract: Natural sesquiterpene synthases have evolved to make complex terpenoids by quenching reactive carbocations either by proton transfer or by hydroxylation (water capture), depending on their active site. Germacradien-11-ol synthase (Gd11olS) from Streptomyces coelicolor catalyzes the cyclization of farnesyl diphosphate (FDP) into the hydroxylated sesquiterpene germacradien-11-ol. Here, we combine experiment and simulation to guide the redesign of its active site pocket to avoid hydroxylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…Especially, the mutation of H320 gave pronounced effects with significantly reduced activity and a product shift towards isolepidozene ( 10 , Scheme 5 ). 32 In the corresponding position of EIZS a Phe residue is found. Its exchange (F332A) showed a strongly reduced catalytic activity with formation of 37% 19 (Scheme 6 ).…”
Section: Residues Contouring the Active-site Cavitymentioning
confidence: 99%
See 3 more Smart Citations
“…Especially, the mutation of H320 gave pronounced effects with significantly reduced activity and a product shift towards isolepidozene ( 10 , Scheme 5 ). 32 In the corresponding position of EIZS a Phe residue is found. Its exchange (F332A) showed a strongly reduced catalytic activity with formation of 37% 19 (Scheme 6 ).…”
Section: Residues Contouring the Active-site Cavitymentioning
confidence: 99%
“…14 For Gd11olS, similar observations were made with G188A yielding the neutral intermediate 11 with strongly reduced activity, while G188V was inactive. 32 Thus, in both cases, exchange of the effector against Ala seems to prevent reprotonation of the neutral intermediate, while exchange against Val completely disrupts enzyme activity. Also for sestermobaraene synthase, exchange of the effector (G184L) resulted in abolished production.…”
Section: Residues For Substrate Binding and Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study on the STS germacradien‐11‐ol synthase revealed that subtle changes in the water binding regions of TSs can have profound effects on the hydroxylation activities exhibited by these enzymes. [78] …”
Section: Computational Chemistry Of Terpene Synthasesmentioning
confidence: 99%